Report from the interior - Auster, Paul 1947-2024 (Picador, 2014)
"Having recalled his life through the story of his physical self in Winter journal ... novelist Paul Auster now remembers the experience of his development from within through the encounters of his interior self with the outer world ... From his baby's-eye view of the man in the moon, to his childhood worship of the movie cowboy Buster Crabbe, to the composition of his first poem at the age of nine, to his dawning awareness of the injustices of American life, [this book] charts Auster's moral, political, and intellectual journey as he inches his way toward adulthood through the postwar 1950s and into the turbulent 1960s"--